THE ROLE OF CHINESE MIGRANTS IN ACCELERATING BORDER CITY DEVELOPMENT - Amorisa Wiratri (Jurnal Kajian Wilayah, 2020)
The migration of Chinese labours to Southeast Asian countries has become a huge issue lately. This study examines whether all Chinese migrants bring negative impacts to other countries. This research argues that Chinese migrants have a compelling part in support of development in the border area, particularly economic development. This research was conducted in Mong Cai, a border city between Vietnam and China. Using qualitative approach as methodology, the data are collected through observation, in-depth interviews, and review of the literature. The result found that Chinese migrants bring advantages in Mong Cai city, including support city development and improve the local economy.